Foreword and Supplemental Information, Swine Day - R. D. Goodband; M. D. Tokach; S. S. Dritz; J. M. DeRouchey; J. C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2016)
It is with great pleasure that we present the 2016 Swine Industry Day Report of Progress. This report contains updates and summaries of applied and basic research conducted at Kansas State University during the past year. We hope that the information will be of benefit as we attempt to meet the needs of the Kansas swine industry.
Keywords: swine